2021
DOI: 10.1093/nar/gkab842
|View full text |Cite
|
Sign up to set email alerts
|

USP37 regulates DNA damage response through stabilizing and deubiquitinating BLM

Abstract: The human RecQ helicase BLM is involved in the DNA damage response, DNA metabolism, and genetic stability. Loss of function mutations in BLM cause the genetic instability/cancer predisposition syndrome Bloom syndrome. However, the molecular mechanism underlying the regulation of BLM in cancers remains largely elusive. Here, we demonstrate that the deubiquitinating enzyme USP37 interacts with BLM and that USP37 deubiquitinates and stabilizes BLM, thereby sustaining the DNA damage response (DDR). Mechanistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
0
15
1
Order By: Relevance
“…In recent years, DDR pathway has attracted more and more attention from clinical medicine and translational medicine due to its driving role in tumor genesis and guiding role in tumor precision therapy. DDR pathway has been extensively studied in breast cancer 19 , ovarian cancer 20 , prostate cancer 21 , pancreatic cancer 22 and other cancers, while its guiding significance in the diagnosis and treatment of liver cancer remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, DDR pathway has attracted more and more attention from clinical medicine and translational medicine due to its driving role in tumor genesis and guiding role in tumor precision therapy. DDR pathway has been extensively studied in breast cancer 19 , ovarian cancer 20 , prostate cancer 21 , pancreatic cancer 22 and other cancers, while its guiding significance in the diagnosis and treatment of liver cancer remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that CYLD promotes necroptosis after deubiquitination of RIP1 in necrosomes 38,43 . USP37 can regulate BLM RecQ like helicase deubiquitination and stabilises its expression, thereby maintaining the DNA damage response in BC cells 44 . Sun found that USP36 deubiquitinates c‐Myc in the nucleolus and acts downstream of c‐Myc to promote BC proliferation 45 .…”
Section: Discussionmentioning
confidence: 99%
“… 43 Besides, USP37 was also demonstrated to deubiquitinate and stabilize BLM, a human RecQ helicase, further sustaining the DNA damage response (DDR) and resulting in chemotherapy resistance. 44 …”
Section: Discussionmentioning
confidence: 99%